Chemical Advances in Therapeutic Application of Exosomes and Liposomes - Chew, Boon C.; Liew, Fong Fong; Tan, Hsiao Wei; Chung, Ivy (Current Medicinal Chemistry, 2022)
Exosomes and liposomes are vesicular nanoparticles that can encapsulate functional cargo. The chemical similarities between naturally occurring exosomes and synthetic liposomes have accelerated the development of exosome mimetics as a therapeutic drug delivery platform under physiological and pathological environments. To maximise the applications of exosomes and liposomes in the clinical setting, it is essential to look into their basic chemical properties and utilise these characteristics to optimise the preparation, loading, modification and hybridisation. This review summarises the chemical and biological properties of both exosomal and liposomal systems as well as some of the challenges related to their production and application. This article concludes with a discussion on potential perspectives for the integration of exosomal and liposomal technologies in mapping better approaches for their biomedical use, especially in therapeutics.
Keywords: biogenesis